Effective removal of lead(II) from wastewater by amine-functionalized magnesium ferrite nanoparticles - Jeeranan Nonkumwong (2018)
© The Royal Society of Chemistry 2016. Mesoporous amine-functionalized magnesium ferrite nanoparticles (MgFe2O4-NH2NPs), with maximum magnetization of around 35 emu g-1, were successfully synthesized and simultaneously functionalized under a refluxing condition by using ethanolamine as a surface modifier. The grafting of amine groups onto the MgFe2O4NPs was clearly confirmed by the Fourier transform infrared spectrum. Adopting the MgFe2O4-NH2NPs as a magnetic nanoadsorbent for Pb2+removal from simulated wastewater containing heavy metals is reported. Characterizations of the adsorption ability of MgFe2O4-NH2nanoadsorbent as a function of aqueous solution pH, initial Pb2+concentration and agitating time, as well as their adsorption kinetics and adsorption isotherms, were also performed. The adsorption of 25 mL of 10 mg L-1Pb2+initial concentration onto 25 mg of MgFe2O4-NH2nanoadsorbent reached equilibrium within 10 min at pH 4 with 99% removal efficiency. Kinetics and isotherms of the adsorption were fitted with pseudo-second-order model and Langmuir model, respectively, indicating the strong chemisorption through coordinative bond formation between the amine groups and Pb2+ions. This MgFe2O4-NH2nanoadsorbent possesses a maximum capacity, calculated from Langmuir equation, of around 135.1 mg g-1, which is higher than those of typical amine-functionalized adsorbents. Also, the selectivity experiments show that the MgFe2O4-NH2nanoadsorbent provides higher selectivity coefficient values for Pb2+than Ca2+, Cd2+, Zn2+, Cu2+and Ni2+.